Occupied reflections: audience as performers - Sara Carvalho (Revista Vortex, 2020)
New music is often perceived as challenging, and many times generates controversial opinions. Nevertheless, it allows for some non-obvious relationships between composers, performers, and listeners. Finding more effective ways to engage listeners into new music could be an alternative way to reach out to further audiences. This paper aims to discuss and give examples of how the audience was integrated as a performer in a new music performance, more specif ically in the piece “occupied mirrors”, for toy piano and audience (composed by the author of the paper). The piece was thought through and planned in such a way that it invited the audience to become active performers, part of the musical plot as music makers. Conclusions suggest that what was asked from the audience opened up a unique new music experience, as they had to follow instructions and actively participate in the construction of the sound.